Pullulan-based nanoparticles: future therapeutic applications in transmucosal protein delivery - Rodrigues, Susana (2013)
Current advances in the field of drug delivery are aimed at finding adequate strategies for the administration of different drugs. Transmucosal delivery is the first-line option for the systemic delivery of many drugs, including proteins, a group of molecules with recognised therapeutic potential and wide range of applications (drug and genetic therapy, immunisation, among others).